Incidence of transmissible diseases in a network of assisted reproduction clinics throughout Queensland. (14th July 2015) - Harrison, Keith; Darling, Nicky; Vargas, Karen; Irving, Jacquelyn; Osborn, Jeremy; Yazdani, Anusch; Molloy, David
<x xml:space="preserve">Abstract</x> In assisted reproduction, knowledge of the presence of transmissible disease assists diagnosis and permits appropriate risk minimisation. The overall incidence was lowest in the Brisbane full‐cost clinic and highest in the Springwood low‐cost clinic. Male partners predominated over females, particularly in the low‐cost clinic. Hepatitis C was the most commonly detected infection with the highest incidence in the low‐cost clinic. HIV was the least commonly detected infection amongst those tested.